2017
DOI: 10.1128/jvi.00450-17
|View full text |Cite
|
Sign up to set email alerts
|

A Naturally Occurring Recombinant Enterovirus Expresses a Torovirus Deubiquitinase

Abstract: Enteroviruses (EVs) are implicated in a wide range of diseases in humans and animals. In this study, a novel enterovirus (enterovirus species G [EVG]) (EVG 08/NC_USA/2015) was isolated from a diagnostic sample from a neonatal pig diarrhea case and identified by using metagenomics and complete genome sequencing. The viral genome shares 75.4% nucleotide identity with a prototypic EVG strain (PEV9 UKG/410/73). Remarkably, a 582-nucleotide insertion, flanked by 3C pro cleavage sites at the 5= and 3= ends, was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
72
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 91 publications
3
72
0
Order By: Relevance
“…The viral 3C pro protease trims the EV‐G precursor polyprotein posttranslationally into the 2C and 3A proteins at a well‐defined cleavage sequence (ALFQ↓GPPT) (Blom, Hansen, Brunak, & Blaas, ). Furthermore, a previous study using reverse genetics revealed that the US EV‐G17‐PLCP strain functionally produces the exogenous PLCP gene in virus‐infected cells, demonstrating its own ALFQ↓GPPV and AEFQ↓GPPT sequences as the putative cleavage sites (Shang et al., ). Considering the sequence similarity of the putative cleavage sites including GPPT−ALFQ, GPPA−ALFQ, and GPPE−ALPQ among global strains (Conceição‐Neto et al., ; Knutson et al., ; Tsuchiaka et al., ), therefore, the cleavage of the inserted PLCP gene appears to be guaranteed using each corresponding cleavage sequence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The viral 3C pro protease trims the EV‐G precursor polyprotein posttranslationally into the 2C and 3A proteins at a well‐defined cleavage sequence (ALFQ↓GPPT) (Blom, Hansen, Brunak, & Blaas, ). Furthermore, a previous study using reverse genetics revealed that the US EV‐G17‐PLCP strain functionally produces the exogenous PLCP gene in virus‐infected cells, demonstrating its own ALFQ↓GPPV and AEFQ↓GPPT sequences as the putative cleavage sites (Shang et al., ). Considering the sequence similarity of the putative cleavage sites including GPPT−ALFQ, GPPA−ALFQ, and GPPE−ALPQ among global strains (Conceição‐Neto et al., ; Knutson et al., ; Tsuchiaka et al., ), therefore, the cleavage of the inserted PLCP gene appears to be guaranteed using each corresponding cleavage sequence.…”
mentioning
confidence: 99%
“…The length of the inserted PLCP sequence varied among strains from different geographical locations (194/223‐aa, 212‐aa, and 211/217‐aa for the US, Belgium, and Japanese strains respectively) (Figure b). The PLCP sequence of Korean EV‐G only shared 75.0%−89.3% aa sequence identity with other recombinant EV‐G1, ‐G2, and ‐G17 strains, exhibiting the highest identity with the US EV‐G17 strain 08/NC_USA/2015 (Shang et al., ). The viral 3C pro protease trims the EV‐G precursor polyprotein posttranslationally into the 2C and 3A proteins at a well‐defined cleavage sequence (ALFQ↓GPPT) (Blom, Hansen, Brunak, & Blaas, ).…”
mentioning
confidence: 99%
“…In addition to type 1 recombinant EV-G, second type of recombinant EV-G (we call type 2 recombinant EV-G in this study), which carried the PLCP gene in place of viral structural genes, has been identified in a Chinese pig farm (Wang et al, 2018). The PLCP gene is encoded in the ORF1 of the genome of torovirus, a member of family Coronaviridae, and the order Nidovirales (Conceição-Neto et al, 2017;Knutson et al, 2017;Shang et al, 2017;Tsuchiaka et al, 2017;Wang et al, 2018). The PLCP of nidoviruses serves as a protease to cleave viral gene 1 polyproteins to mature proteins (Mielech et al, 2014).…”
Section: Figmentioning
confidence: 99%
“…The PLCP of nidoviruses serves as a protease to cleave viral gene 1 polyproteins to mature proteins (Mielech et al, 2014). It also has functions of deubiquitinating and deISGylating (interferonstimulated gene15-removing) enzymes, which plays important roles in viral pathogenesis by acting as an innate immunity antagonist (Shang et al, 2017).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation